From Radical to Moderate: The Role of IPM Within Muslim Youth - Yanuri, Yusuf Rohmat (Universitas Muhammadiyah Yogyakarta, 2024)
Muhammadiyah members' ideologies vary. There are conservative, moderate, and liberal. Studies by Fealy, Zulian, and Burhani pointed out that few Muhammadiyah members adhere to radical views even though the majority is certainly moderate. In this paper, I want to focus on how Muhammadiyah, particularly Ikatan Pelajar Muhammadiyah (IPM, Muhammadiyah School Student Association) shifts the paradigm of some young students in Indonesia from radical to moderate. IPM is an autonomous organization (organisasi otonom, ortom) under Muhammadiyah. This research uses a qualitative approach, focusing on an in-depth understanding of the role of IPM in changing student paradigms. The choice of qualitative methods is suitable for exploring students' views and experiences in detail. The research involved several sources who had experienced a paradigm shift from radical to moderate due to direct contact with IPM programs. I called the efforts of IPM in this field ‘unintentional change’ due to there are just a few IPM events that were intended to solve the problem of radicalization. IPM focuses on other things, such as literacy, ecology, peer mentoring, mental health, culture, and sport. However, through these events, IPM could provide a good environment to decrease the radicalism level and change it to moderate.